A gallium telluride quantum dots bioelectrode system for human epidermal growth factor receptor-2 (Her2/neu) oncogene signalling. Issue 15 (7th August 2015) - Fuku, Xolile; Singh, Baljit; Ajayi, Rachel F.; Jijana, Abongile N.; Baker, Priscilla; Dempsey, Eithne; Iwuoha, Emmanuel
<x xml:space="preserve">Abstract</x> A new biosensor system is presented for the determination of human epidermal growth factor receptor 2 (Her2/neu) biomarker that is overexpressed in human breast cancer.